Extra-Peritoneal versus Trans-Peritoneal Open Radical Cystectomy - Comparison of Two Techniques in Early Post-Operative Complications - Soleimani, Mohammad; Moradkhani, Ehsan; Masoumi, Navid; Gholivandan, Jafar (Urology Journal, 2020)
Purpose: The conventional Trans-Peritoneal Radical Cystectomy (TPRC) harbors numerous postoperative complications, the most prevalent of which are Gastrointestinal (GI) problems. To reduce these morbidities we introduced our own version of extra-peritoneal approach and compared it with the conventional method. Materials and Methods: In a cross-sectional observational retrospective design, eligible bladder cancer patients whom underwent Extra-Peritoneal Radical Cystectomy (EPRC) or TPRC in our center, were considered for this study and were compared for early post-operative complications . Results: Ninety nine patients in TPRC and 81 in EPRC were compared. The two techniques differed in their mean operation time (298.2±37.8 min TPRC vs. 262.8±37.2 min EPRC , P: 0.001). Early GI complications were lower in EPRC groups, including oral intake intolerance ( 21 vs. 8, P: 0.04), ileus (19 vs. 8, P: 0.04), intestinal obstruction (3 vs. 0, P: 0.04) and anastomosis leak (8 vs. 1, P: 0.01). Urine leak (14 vs.7 , P: 0.02) and wound related complications (19 vs. 6 , P: 0.02) also favored EPRC group. Conclusion: The extra-peritoneal technique is beneficial in reducing the post operative morbidity, especially the more prevalent GI complications. This approach is functionally safe and allows preservation of the peritoneal integrity.